Black Mecca: The African Muslims of Harlem By Zain Abdullah (New York: Oxford University Press, 2010. hbk. 240 pages.) (American Journal of Islam and Society, 2012)
Black Mecca undoubtedly is a new contribution to the literature on Islamin America. It contributes to a better understanding of AfricanMuslim immigrants in the United States. Only a few books have beenpublished on African immigrants in the United States, and Black Meccadefinitely adds a new dimension to the discussions of African immigrantroles in the United States and to Islamic thought in general.This work will allow readers to recognize that West African Muslimsare not just earning incomeh in the United States; they are actually contributingto the development of Harlem in New York. Often times, many immigrantswould reside in low-class residences until they become affluent, then they would leave the area. These African Muslims consider Harlemtheir home; they have turned it into a thriving business area; they residethere and develop it by building schools and mosques for their community ...